Angiogenic potential of airbrushed fucoidan/polycaprolactone nanofibrous meshes - Reys, Lara Priscila Lopes (2021)
Implantation of biomaterials and hybrid constructs in tissue engineering approaches presents major limitations such as inflammatory reaction and the lack of vasculature integration. Therefore, new strategies are needed to enhance implant function, immune protection, and revascularization. In this work, we developed fibrous meshes composed of fucoidan (Fu), a sulfated polysaccharide extracted from brown algae, and polycaprolactone (PCL), a synthetic biodegradable polymer, using the airbrush technique. The chemical characterization by FTIR, EDS, and XPS confirmed the presence of the two polymers in the structure of airbrushed nanofibrous meshes (ANFM). Moreover, these nanofibrous exhibited good wettability and mechanical properties envisaging their application as templates for biomaterials and cell culture. The developed ANFM were directly cultured with human pulmonary microvascular endothelial (HPMEC-ST1.6R) cells for up to 7 days. Biological results demonstrated that ANFM comprising Fu promoted cellular attachment, spreading, and proliferation of human endothelial cells. The angiogenic potential of ANFM was further evaluated by onplantation of PCL and PCL/Fu ANFM in chick chorioallantoic membrane (CAM). In ovo and ex ovo results showed that the incorporation of Fu increased the proangiogenic potential of ANFM. Altogether, the results suggest that airbrush biocomposite meshes could be used as a biomaterial substrate to promote vascularization.